To compare the intercepts of the functions \( f(x)=x^3+1 \) and \( g(x)=x+1 \), we will need to find their x-intercepts and y-intercepts.
For \( f(x)=x^3+1 \)
-
Y-intercept: This occurs when \( x = 0 \). \[ f(0) = 0^3 + 1 = 1 \] Thus, the y-intercept is \( (0, 1) \).
-
X-intercept: This occurs when \( f(x) = 0 \). \[ x^3 + 1 = 0 \implies x^3 = -1 \implies x = -1 \] Thus, the x-intercept is \( (-1, 0) \).
For \( g(x)=x+1 \)
-
Y-intercept: This occurs when \( x = 0 \). \[ g(0) = 0 + 1 = 1 \] Thus, the y-intercept is \( (0, 1) \).
-
X-intercept: This occurs when \( g(x) = 0 \). \[ x + 1 = 0 \implies x = -1 \] Thus, the x-intercept is \( (-1, 0) \).
Results Summary
- Y-intercepts: Both functions have a y-intercept of \( (0, 1) \).
- X-intercepts: Both functions have an x-intercept of \( (-1, 0) \).
Conclusion
Based on the intercepts determined:
- Both functions have an x-intercept of \( (-1, 0) \) and a y-intercept of \( (0, 1) \).
Therefore, the correct statement is:
Both functions have an x-intercept of (-1, 0) and a y-intercept of (0, 1).